2006
DOI: 10.2355/isijinternational.46.1845
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Assessment of Slab Centre Segregation as a Tool to Control Slab Continuous Casting with Soft Reduction

Abstract: Fig. 12.Measured and calculated l 2 -spacings over half the slab thickness and segregation coefficient for Mn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Work was reported in the literature whereby spark-optical emission spectrometry was used to map segregation on large cast samples [17]. However, LIBS offers two additional advantages for the mapping of segregation on cast samples.…”
Section: Segregation Mapping By Libsmentioning
confidence: 99%
“…Work was reported in the literature whereby spark-optical emission spectrometry was used to map segregation on large cast samples [17]. However, LIBS offers two additional advantages for the mapping of segregation on cast samples.…”
Section: Segregation Mapping By Libsmentioning
confidence: 99%
“…MECHANICAL soft reduction (MSR) has been shown in industrial practice to reduce centerline/axial segregation in slab and bloom castings [1][2][3][4][5][6][7][8][9][10] ; however, control of the MSR process remains a trial and error process in plant operations. Empirical knowledge ( Figure 1) has shown that satisfactory MSR efficiency can be achieved when MSR is positioned correctly on the strand and carried out with the appropriate reduction intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Centerline segregation of slabs relates partly to macrosegregation and partly to the shrinkage of melt, the formation of small shrinkage holes and, occasionally, the formation of inclusions [5][6][7][8] . In continuous casting centerline segregation develops in the middle part of the slab due to solidification and transformation processes, to fluid flow and also to constrained liquid supply, which is necessary for solidification shrinkage compensation.…”
Section: Nature Of the Centerline Segregationmentioning
confidence: 99%
“…The latter one produces a relatively well quantifiable result. Because of the connection between the amount of shrinkage holes and the level of macrosegregation 7) , the application of image analysis method and characterization of centerline segregation of the slabs by the porosity level is widely accepted by industry. Despite the high ratio of plastic deformation, strips hot rolled from slabs with centerline segregation contain, in a modified form, the consequences of this type of inner defect 9) .…”
Section: Nature Of the Centerline Segregationmentioning
confidence: 99%
See 1 more Smart Citation